Herbal Medicine Use During Pregnancy: A Review of the Literature With a Special Focus on Sub-Saharan Africa - El Hajj, Magalie; Holst, Lone (Frontiers in Pharmacology, 2020)
Herbal medicine use has grown considerably worldwide among pregnant women, and is particularly widespread in sub-Saharan Africa. However, herbal medicines used across sub-Saharan Africa are associated with important research gaps and a lack of regulatory framework. This is particularly problematic, as herbal medicine use during pregnancy raises several concerns attributed to the herbal ingredient itself, conventional drug-herbal medicine interactions, and contamination or adulteration of herbal remedies. Moreover, several local herbal remedies used by sub-Saharan African pregnant women have never been botanically identified. In this review, an overview of the practice of herbal medicine, including the regulations, challenges and overall safety, is provided. Then, we discuss the prevalence of herbal medicine use during pregnancy across different sub-Saharan African countries, as well as the indications, adverse outcomes, and effectiveness of the most commonly used herbal medicines during pregnancy in that region.